1992
DOI: 10.1002/jemt.1070210104
|View full text |Cite
|
Sign up to set email alerts
|

Localization of adenovirus DNA by in situ hybridization electron microscopy

Abstract: Biotinylated deoxyadenosine triphosphate (dATP) (Bio-7-dATP) and 3H deoxythymidine triphosphate (dTTP) labeled adenovirus DNA were hybridized in situ to thin sections of Lowicryl K4M-embedded and whole-mount extracted HeLa cells infected with adenovirus. The biotinylated probe was detected by exposing the extracted cells or sections to antibodies against biotin followed by colloidal gold-conjugated secondary antibodies and then critical-point dried while 3H-dTTP labeled probe by electron microscopic autoradiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Up to now, no progeny adenoviruses were observed in the cytoplasm under normal preparative conditions of cells up to 24 h post-infection. In contrast, the preservation of the topological distribution of cellular DNA and viral DNA and the total absence of dissociation of paracrystalline arrays of viruses emphasized the crucial role of the nuclear matrix in viral development (Younghusband and Maundrell, 1982;Khitoo et al, 1986;Jiao et al, 1992). In a previous study bearing on the respective distribution of cellular DNA and viral genomes following mild loosening of the nucleoproteins of cells at 17 h post-infection (Besse and Puvion-Dutilleul, 1994b), we observed that mature viruses which are normally loosely dispersed in the virus-induced electron-translucent region of the infected nucleus were free and able to leave the nucleus during the spreading procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, no progeny adenoviruses were observed in the cytoplasm under normal preparative conditions of cells up to 24 h post-infection. In contrast, the preservation of the topological distribution of cellular DNA and viral DNA and the total absence of dissociation of paracrystalline arrays of viruses emphasized the crucial role of the nuclear matrix in viral development (Younghusband and Maundrell, 1982;Khitoo et al, 1986;Jiao et al, 1992). In a previous study bearing on the respective distribution of cellular DNA and viral genomes following mild loosening of the nucleoproteins of cells at 17 h post-infection (Besse and Puvion-Dutilleul, 1994b), we observed that mature viruses which are normally loosely dispersed in the virus-induced electron-translucent region of the infected nucleus were free and able to leave the nucleus during the spreading procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the interactions of some viruses and viral dsDNA and ssDNA molecules with nuclear matrix and changes in nucleo-cytoplasmic transport occur, therefore, in cells at 41 h post-infection allowing the escape of viral nucleic acid molecules and viruses from the nucleus to the cytoplasm. Adenoviral DNA normally is tightly bound to the nuclear matrix of productively infected cells (Younghusband and Maundrell, 1982;Khitoo et ~2, 1986;Jiao et al, 1992). Adenoviral DNA normally is tightly bound to the nuclear matrix of productively infected cells (Younghusband and Maundrell, 1982;Khitoo et ~2, 1986;Jiao et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization provides an opportunity to determine the relative position of molecules that are not resolvable by LM. Non-radioactive probes provide high spatial resolution, rapid signal detection, and precise localization uiao et al., 1992;Troxler et al, 1990). Moreover, RNA probes appear to give a lower nonspecific background than DNA probes, and also give better signal intensity (Morrell, 1989;Meyerowitz, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy in situ hybridization was carried out using the method of Jiao et al [10]. rDNA (fragments of 4.2, 2.2 and 1.6 kb) was recovered and labelled with 11‐biotin‐dATP as probe.…”
Section: Methodsmentioning
confidence: 99%